A CONTRASTIVE ANALYSIS BETWEEN ENGLISH AND INDONESIAN NEGATIONS: A CASE OF NEGATIVE MARKERS - Sulaiman, Masagus (Universitas Muhammadiyah Palembang, 2020)
This research is aimed at determining the similarities, dissimilarities, and possible difficulties faced by Indonesian and English speaking students as learning negations and also the recommendations to TEFL. The descriptive-qualitative method was used. The documentation technique was applied in collecting the data. To analyze the data, the researcher used a descriptive analysis. The results showed that there were six similarities and four dissimilarites between English and Indonesian negations. The six similarities were in rejection or denial with verbs, adjectives, nouns, adverbs, “No” followed by nouns, and incomplete or undone action. The four dissimilarities were in confixation, suffixation, short prohibition and strong objection. The possible difficultes faced by English speaking students was in confixation, while Indonesian students’ was in suffixation and strong objection. The dissimilarities make recommendations to TEFL teachers to design teaching materials of English grammar that enable students understand negations.